The Effect of Academic Resilience on Student Procrastination Among Junior High School Students - Lestari, Liana; Taridi, Taridi; Ardianto, Hendri; Pembangunan, Heldy Ramadhan Putra; Adeoye, Moses Adeleke (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
Academic procrastination is a widespread behavioral issue among junior high school students, commonly marked by delays in completing schoolwork, preference for leisure activities such as gaming or social media, and difficulties in managing time effectively. Academic resilience the ability to persist through academic challenges is considered a potential protective factor against procrastination. This study investigates the effect of academic resilience on student procrastination among junior high school students in Pesawaran, Indonesia. A quantitative approach was employed using a survey method, with data collected through a 74-item Likert-scale questionnaire. A total of 163 students were selected using proportionate stratified random sampling. The instrument was tested for validity and reliability prior to analysis. Data were analyzed using simple linear regression. The results indicate that academic resilience significantly affects student procrastination (p < 0.05), with a coefficient of determination (R²) of 0.782. This means that 78.2% of the variance in procrastination can be explained by academic resilience, while the remaining 21.8% is attributed to other unmeasured factors. These findings underline the importance of integrating resilience-building strategies into educational interventions to mitigate procrastination behaviors. The study contributes to the literature on student motivation and offers practical insights for educators and school counselors seeking to enhance student engagement and academic discipline.